Penelusuran Pustaka Tentang Trauma Perempuan Korban Perdagangan Seksual - Rachmadhani, Titania Caesary; Liana Puspita, Syntia Agung; Cahyanti, Ika Yuniar; Herdiana, Ike (Fakultas Psikologi Universitas YARSI, 2024)
Sexual trafficking is one of the scariest living conditions and is often a traumatic experience for victims who experience it. The traumatic experiences experienced by victims of sexual trafficking often lead to long-term trauma and lead to a variety of mental disorders. The purpose of writing this article is to explain how trauma faced by victims of sexual trafficking and the handling of trauma that can be given to victims of sexual trafficking. This article is based on a literature review and research journal accessed from the official websites of Google Scholar, Science Direct, Research Gate, and SAGE Publisher. A literature review revealed that there are many impacts experienced by victims of sexual trafficking. These impacts include physical impacts, psychological and social impacts, so that victims of sexual trafficking often experience trauma even though they have been released from the trap of sexual trafficking. Forms of trauma faced by victims of sexual trafficking such as experiencing anxiety, feelings of guilt, loss of self-confidence and not infrequently experiencing symptoms of post-traumatic stress. Researchers also discussed the traumatic experiences experienced by victims of sexual trafficking. The existence of social support from the closest people such as family and friends, assistance from experts and professionals such as psychologists is considered able to reduce the trauma of victims of sexual trafficking